Resting plasma and salivary IL-6 concentrations are not correlated in distance runners - Cox, A. J.; Pyne, D. B.; Gleson, M.; Callister, R. (European Journal of Applied Physiology, 2008)
Measurement of IL-6 has been widely undertaken to examine inflammatory and immune responses to exercise. Use of salivary IL-6 offers an alternative to the invasive collection procedures required for IL-6 measurement in plasma samples. Rarely, however, has the degree of association between plasma and salivary IL-6 been reported. The aim of the current study was to investigate the relationship between resting salivary and plasma IL-6 concentrations in 45 trained distance runners (36 males, 9 females; age: 35.1 ± 8.0 y, mean ± SD). Plasma and saliva samples were collected from athletes under resting conditions. Plasma IL-6 concentrations were determined using a Bioplex suspension array system and commercially available reagents. Salivary IL-6 concentrations were determined using a commercially available high-sensitivity ELISA kit. At rest, the mean (± SD) plasma IL-6 concentration was 3.43 ± 3.75 pg mL-1 compared to a mean salivary IL-6 concentration of 1.80 ± 4.25 pg mL-1. IL-6 concentrations in plasma and saliva samples were not correlated (r = -0.031, p = 0.85). At rest, salivary IL-6 concentrations do not reflect plasma IL-6 concentrations. The potential for salivary IL-6 to act as a surrogate marker for plasma IL-6 responses when examining inflammatory and immune responses to exercise, therefore, appears unlikely.